Dealer stock books - J. Paul Getty Trust (2014)
[Dt.:] In der frei zugänglichen Online-Datenbank sind die Einträge aus den Lagerbüchern der Knoedler Galerie und der Goupil & Cie Galerie in Paris verzeichnet. Die Einträge sind aus den Jahren 1872-1970 bzw, 1846-1919. - [Engl.:] The Getty Research Institute has launched an expanded Dealer Stock Books database that provides free online access to records created from the Knoedler Gallery painting stock books. Books 1 through 6, dating from 1872 to 1920, and stock books 7 through 11, covering 1921-1970. Knoedler Gallery in New York was a central force in the evolution of an art market in the U.S. Together with over 43,700 records from another prominent gallery, Goupil & Cie and Boussod, Valadon & Cie in Paris (1846–1919), this expanded database can be used to reconstruct the itineraries of thousands of paintings that crossed the Atlantic.